The Prevalence, Burden, and Treatment of Severe, Frequent, and Migraine Headaches in US Minority Populations: Statistics From National Survey Studies. Issue 2 (3rd February 2015) - Loder, Stephen; Sheikh, Huma U.; Loder, Elizabeth
<x xml:space="preserve">Abstract</x> Background The prevalence and burden of migraine and other severe headaches in the US population as a whole is well documented. Prevalence and treatment patterns in US racial and ethnic minorities, however, have received less attention. We sought to assemble and compare this information as identified in large, nationally representative studies. Methods We searched for summary statistics from studies performed in the United States between 1989 and 2014. Included studies had to provide population‐based, nationally or broadly representative information on the prevalence, burden, or treatment of severe or frequent headache or migraine in adult US Blacks, Hispanics, Native Americans, or Asians. Results Nine studies were included in the review. Prevalence data from the National Health Interview Survey (NHIS) provide the most comprehensive information for major racial and ethnic groups. The average prevalence of severe headache or migraine from 2005 to 2012 NHIS was 17.7% for Native Americans, 15.5% for Whites, 14.5% for Hispanics, 14.45% for Blacks, and 9.2% for Asians. Severe headache or migraine prevalence was higher in females of all races and ethnic groups compared with males and across all included studies. Female to male prevalence ratios from the 2005‐2012 NHIS were 2.1 for Whites, 2.5 for Hispanics, 2.1 for Blacks, and 2.0 for Asians. Among those with chronic migraine (≥15 days of headache per month), prevalence data from the American Migraine Prevalence and Prevention study showed that the prevalence of chronic migraine was highest in Hispanic women (2.26% compared with 1.2% for White females), whereas White males had the lowest prevalence at 0.46%. Data from the National Hospital Ambulatory Care Survey and National Ambulatory Care Survey show that Hispanics make only 89.5 annual ambulatory care visits per 10, 000 population at which they receive a diagnosis of migraine, compared with 176.3 for Whites and 133.2 for Blacks. In contrast, visit rates resulting in a diagnosis of nonspecific headache were more comparable across all groups. Only one study obtained information on selected subgroups within Hispanic and Asian populations. This showed that differences among these subgroups, which suggest composite prevalence estimates for broadly defined racial and ethnic groups such as Asians, may conceal meaningful differences in subgroups, such as Vietnamese or Filipinos. Conclusions In the United States, migraine prevalence is highest among Native Americans, then Whites, followed closely by Hispanics and Blacks. Asians have the lowest prevalence of severe, frequent headache or migraine of the major racial or ethnic groups. Differences in diagnosis and treatment of headache and migraine may indicate racial and ethnic disparities in access and quality of care for minority patients.